2013
DOI: 10.1371/journal.pone.0074070
|View full text |Cite
|
Sign up to set email alerts
|

Structural Interactions within the Default Mode Network Identified by Bayesian Network Analysis in Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is a well-known neurodegenerative disease that is associated with dramatic morphological abnormalities. The default mode network (DMN) is one of the most frequently studied resting-state networks. However, less is known about specific structural dependency or interactions among brain regions within the DMN in AD. In this study, we performed a Bayesian network (BN) analysis based on regional grey matter volumes to identify differences in structural interactions among core DMN regions in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 59 publications
1
32
0
1
Order By: Relevance
“…A second interesting aspect is the relationship between the left hippocampus and right inferior temporal gyrus, which was highlighted by k -core decomposition. This result is in agreement with the study of Wang et al ( 132 ), which found that the interaction between these two areas is typical of AD. Of note, Wang et al ( 132 ) examined 80 pathological subjects using Bayesian network analysis and prior-defined regions of interest, while the present study has applied a meta-analytical approach on a substantially bigger VBM database of 883 patients diagnosed with AD.…”
Section: Discussionsupporting
confidence: 94%
“…A second interesting aspect is the relationship between the left hippocampus and right inferior temporal gyrus, which was highlighted by k -core decomposition. This result is in agreement with the study of Wang et al ( 132 ), which found that the interaction between these two areas is typical of AD. Of note, Wang et al ( 132 ) examined 80 pathological subjects using Bayesian network analysis and prior-defined regions of interest, while the present study has applied a meta-analytical approach on a substantially bigger VBM database of 883 patients diagnosed with AD.…”
Section: Discussionsupporting
confidence: 94%
“…Similarly, Wang and colleagues recently used Bayesian network classifiers to integrate data from multiple platforms to identify biomarkers confirming previously published results [31]. Previous research using Bayesian networks to define marker connections in AD has primarily been performed using imaging data [28, 29], however these methods have not defined the posterior probability of both within and between group connections.…”
Section: Discussionmentioning
confidence: 62%
“…In addition, Jacobs et al demonstrated that grey matter atrophy in inferior parietal lobule was connected to the prefrontal cortices [ 46 ]. Recently, Wang and colleagues employing Bayesian network models and integrating grey matter volume information from multiple brain regions found increased correlations from Left inferior temporal cortex to Left hippocampus, Left hippocampus to Right inferior temporal cortex, Right hippocampus to Right inferior temporal cortex, and Right inferior parietal cortex to Posterior cingulate cortex in AD patients [ 47 ]. The morphological changes in the grey matter in different brain regions abide by covariance pattern, reflecting the DMN network attributes of the human brain, and also suggest that the atrophy of these structures is not independent, but that primary neurodegeneration in one of the structures that could lead to secondary degeneration of regions connected to it.…”
Section: Discussionmentioning
confidence: 99%